Analysing barriers of digitalization in apparel sector: a fuzzy DEMATEL approach - ÖZBEK, AHMET (My University, 2023)
The digital transformation process entails the creation of new business models, processes, software, and technologically advanced systems. This study aims to analyze the barriers that businesses in the apparel sector face during the process of digitalization. So far, no comprehensive study has been found in the literature that analyses how these barriers interact with each other to make better decisions for digital transformation. This study initiates by conducting an identification of the barriers faced by companies operating in the apparel sector during their pursuit of digitalization. Then, prioritizing important barriers and the relationships between these barriers are analyzed using the Fuzzy DEMATEL method. Research results showed that lack of expertise, lack of management support, insufficient financial resources and lack of IT system are the four main barriers. It is thought that the development of digitalization in the apparel clothing industry will increase by keeping these barriers in focus.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Tekstil İşletmeciliği ve Yönetimi; Mühendislik ve Teknoloji; Textile Engineering and Technology; Textile Management; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, TEKSTİL; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, TEXTILES